THE COMPARISON OF LPG AND NATURAL GAS ADSORPTION CAPACITY IN CARBON ADSORBENT - Herawan, Safarudin Gazali; Sulaiman, Mohd Yusoff (2008)
The current research focuses on the experimental investigation of carbon adsorbent produced from oil palm shell as a raw material. These carbon materials can be used for catalyst supports and adsorbents because of its prominent characteristics, such as high surface area, relatively uniform pore size, ordered pore structure and good thermal and mechanical stabilities. The objective of the present research is to develop a liquefied petroleum gas (LPG) and methane gas storage as the alternative fuels for vehicles based upon the carbon adsorbents. Carbon adsorbent as a gas storage media for LPG and methane gas are an alternative way to overcome the disadvantages of pressurized vessel such as high-pressure flammable gas content, imension of gas tank, and other dangerous aspects. This research will be conducted by designing and developing the experimental rig for preparing carbon adsorbent, which are consisted of a reactor, tube furnace, suction blower and some accessories. Other process,which is activation carried out in a same reactor, which blanketed by tube furnace where the pyrolysis take place. These research aims are used to the extending application of proposed framework to problem arising in the alternative fuel for vehicles.